If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 = -1.5 + 0.5y Solving -3 = -1.5 + 0.5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-0.5y' to each side of the equation. -3 + -0.5y = -1.5 + 0.5y + -0.5y Combine like terms: 0.5y + -0.5y = 0.0 -3 + -0.5y = -1.5 + 0.0 -3 + -0.5y = -1.5 Add '3' to each side of the equation. -3 + 3 + -0.5y = -1.5 + 3 Combine like terms: -3 + 3 = 0 0 + -0.5y = -1.5 + 3 -0.5y = -1.5 + 3 Combine like terms: -1.5 + 3 = 1.5 -0.5y = 1.5 Divide each side by '-0.5'. y = -3 Simplifying y = -3
| 5x+3x=4x+2 | | 169x^4-196y^6= | | 0.3(30)+.15x=.2(30+x) | | 5x^2+12x-7=0 | | (w-11)w=180 | | 9x-8+3x+6= | | 5x+3x=4x-2 | | 9x^6+21x^3+10= | | 3x*5=3x | | 60+50+x+70=180 | | -8.1(-10.7)= | | -8-(-10.7)= | | -4x+9z=9z+6-3z | | (x^2-36)3=80 | | 4x^2+2xy-6y^2= | | 7(2)+2y=4 | | 2x^2+2y^2-12x-24y+10=0 | | 4u=35-3u | | (4x+34)+(x+36)=180 | | 2x+3(x-1)=4x-25+2x | | 3x^2+-36X+28=0 | | -8z+4z=z+2+7z | | 7(p+7)+p=81 | | 8x-6=8+7x | | -6(x+5)=-6x-36 | | -4+-1B+8x+-2xB=0 | | 2x+-5=x-7 | | 10x^2-11x+5= | | 48x-12=p | | 1/2+(2/33/4)-(4/5*5/6)= | | 4y=5x^2-2 | | 11.3-7.2*f=-3.82 |